Social Support and Academic Motivation as Factors Forming Students' Psychological Resilience: A Study in Central Bangka Regency - Susanto, Chandra; Budiyanto, Sarah Khairunnisa; Kurniawan, Wilona Keegan (Universitas Pahlawan Tuanku Tambusai, 2025)
In Central Bangka Regency, which is the province’s largest tin producer, illegal tin mining has led to a high school dropout rate, a problem that suggests a lack of student resilience against economic and social pressures. While prior studies have explored factors influencing academic resilience, there remains a gap in understanding how family social support and academic motivation specifically impact students in this unique, high-risk environment. This study aims to fill that gap by investigating the relationship between family social support, academic motivation, and the psychological resilience of junior high school students in Central Bangka. Using a mixed-methods approach with a sample of 216 students, quantitative data was gathered through questionnaires and analyzed using descriptive, correlation, and regression techniques. Qualitative data was collected via interviews and thematic analysis. The findings reveal a significant positive correlation between both academic motivation and psychological resilience, as well as social support and psychological resilience. The qualitative results identified key themes, including family support as a “pillar” of resilience, the role of both intrinsic and extrinsic academic motivation, and the powerful influence of illegal tin mining as a risk factor. The study concludes that both internal (academic motivation) and external (social support) factors are crucial for student resilience, although academic motivation has a more dominant influence. The results provide insight for future interventions aimed at promoting healthier educational practices in communities facing similar challenges.